REseau MOllusques des Rendements Aquacoles huitre creuse (REMORA) - Fleury, Pierre-gildas; Cornette, Florence; Claude, Serge; Palvadeau, Hubert; Robert, Stéphane; D'Amico, Florence; Le Gall, Patrik; Vercelli, Catherine (2001)
The monitoring network IFREMER /REMORA is assessing, on a yearly basis, mortality, growth and quality criteria of two oyster batches ("juveniles" = one-year old and "adults" = two-years old), distributed among various stations of the main French oyster areas. Samplings are carried out in March, June, September and December. This network is a tool for trend estimations (geographic and chronological, on the national scale) it must not be considered as an accurate estimation of professional oyster ongrowings. With the exception of Spring mortalities due to poor initial quality of adult oysters and to difficulties in the counting of juveniles, the year 2000 appeared to be a year of low mortality. 2000 is a year of poor growth (61.5 g in average weight in December) only South Brittany performed good final weights (76,9 g in average), Oysters from Thau (Méditerrannée) reached the best growth (96,5 g) but less than the weight of 100 g which was usually obtained in this area. With regard to the oyster quality, the minimum level of meat index for the category "spéciales" was raised in 2000 (10,5 instead of 9), and the number of stations which reached this class was therefore somewhat reduced. The year 2000 was overall characterized by the first decrease of the Polydora index since the REMORA network was set up in 1993. Still very present in juvenile oysters of South Brittany and of Arcachon, the worm Polydora decreased in adult oysters of most areas execepted Brittany. Le réseau IFREMER /REMORA évalue chaque année la mortalité, la croissance et des critères de qualité de 2 lots d'huîtres ("juvéniles" = 1 a n et "adultes" = 2 ans) qui sont répartis entre différentes stations dans les principaux secteurs ostréicoles français. Des échantillonnages sont effectués en mars, juin, septembre et décembre. Ce réseau est un outil d'évaluation des tendances (géographiques et chronologiques, globales à l'échelle nationale) il ne doit pas être perçu comme un estimateur précis des croissances obtenues chez les producteurs. ...